Evaluasi Kepuasan Aplikasi Pelayanan Rakyat Online Denpasar+ Menggunakan End User Computing Satisfaction - Fridayanti, Ni Putu Eka; Dantes, Gede Rasben; Saskara, Gede Arna Jude (Jurnal Teknik Informatika dan Sistem Informasi, 2024)
Denpasar is one of the cities that has implemented an online public service application (PRO Denpasar+), which is currently known as Denpasar Prama Sewaka or DPS. This application ensures that the agencies that are part of it maintain vertical integrity. However, there are still some obstacles, such as the level of implementation satisfaction that has not been identified among active users. This study emphasizes the End User Computing Satisfaction (EUCS) approach, which centers on five key factors that contribute to user satisfaction: content, accuracy, format, ease of use and timeliness in relation to user of satisfaction, which focuses on application evaluation analysis. The study included 30 and 99 respondents active application users who were residents of Denpasar City were selected through purposive sampling and using a Likert scale based on the average score of user satisfaction to measure the levell of satisfaction experienced by each variableewith 14 questions. Based on detailed data analysis, the average satisfaction score for each variable was 4.24 for content, 3.73 for accuracy, 4.23 for format, 4.19 for user-friendliness, and 4.08 for timeliness. In general, these findings indicate that application users are very satisfied with their use. However, its implementation still needs to be refined through revisions. Recommendations for improving the application were compiled using SWOT analysis and based on the achievements of each EUCS variable, respondents' scores from those who disagreed and strongly disagreed, as well as improvement input data provided by respondents through an open questionnaire for providing excellent service to the community.